Pembinaan Pembelajaran Al-Qur'an Metode Bil Qolam Pada Santri Kelas Muroja’ah 2 Di Pondok Pesantren An-Nur Ii Al-Murtadlo Malang - Umaroh, Siti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This community service program aims to improve the Qur’an reading abilities of students in the Muroja’ah 2 class at Pondok Pesantren An-Nur II Al-Murtadlo Malang through training and mentoring using the Bil Qolam method. The activities were carried out in three stages: planning, implementation of the training, and evaluation of the results. The Bil Qolam method was selected because it is practical, gradual, and has been proven effective in helping students understand articulation points (makhraj), lengthening rules, and reading fluency. The results of the program show improvements in students’ Qur’an reading skills in terms of accurate articulation, fluency, and application of basic tajwīd rules. In addition, the program increased the competence and motivation of the accompanying teachers in teaching the Bil Qolam method in a classical setting. Thus, the Bil Qolam training can serve as an effective solution for improving the quality of Qur’an learning in the pesantren environment.